Analysis of the Causes of Exhaust Valve Guide Failure in the Doosan GV 180 TI Engine at PT Bima Golden Powerindo - Aditia Adrian Saputra; Ibnu Hajar; Murdani (International Journal of Science and Environment (IJSE), 2026)
Damage to the exhaust valve guide in the Doosan GV180 TI gas engine can reduce engine performance and reliability, potentially disrupting the continuity of power generation at PT Bima Golden Powerindo, Melibur Site. This study aims to identify the types of exhaust valve guide failures, analyze their contributing factors, and determine corrective action priorities using the Failure Mode and Effects Analysis (FMEA) method and Pareto Diagram. The research employed a case study approach, with data collected through field observations, visual inspections, dimensional measurements of the valve guide, and preventive maintenance records at 750 running hours. The results indicate that the dominant failure modes include excessive wear, ovality, valve sticking, overheating, and lubrication failure. FMEA analysis revealed that excessive wear has the highest risk level, making it the primary priority for corrective action. The main factors contributing to the failures are high operating temperatures, inadequate lubrication, and prolonged engine operating hours. Therefore, periodic inspections, proper lubrication system control, and replacement of the valve guide according to the manufacturer's specifications are recommended to improve engine reliability and extend its service life.